Microstructure and scratch analysis of aluminium thin films sputtered at varying RF power on stainless steel substrates. Issue 1 (1st January 2020) - Mwema, F. M.; Akinlabi, E. T.; Oladijo, O. P.; Krishna, S.
Abstract: Aluminium (Al) thin films (thickness ranging between 500 and 600 nm) were deposited on stainless-steel substrates at varying radio-frequency (RF) power by magnetron sputtering at a constant substrate temperature of 90 ° C. Characterisations were undertaken by field emission scanning electron microscopy (FESEM), optical surface profilometry (OSP), atomic force microscopy (AFM), X-ray diffraction (XRD), selected Fourier-transform infrared spectroscopy (FTIR), nanoindentation, and micro-scratch tests. At high RF powers (300–350 W), there was the formation of less porous, dense, and continuous Al thin films with better resistance to scratch failure. The high roughness on films deposited at 200 and 250 W was due to high porosity and oxides observed on the FESEM micrographs.